PERAN GURU DALAM MEMBENTUK SIKAP DISIPLIN SISWA KELAS I SEKOLAH DASAR MELALUI PENGHARGAAN DAN KONSEKUENSI [THE ROLE OF TEACHERS IN SHAPING THE DISCIPLINE ATTITUDES OF GRADE 1 ELEMENTARY SCHOOL STUDENTS THROUGH REWARDS AND CONSEQUENCES] - Rahmadi, Pitaya; Pancarania, Dinda Putri (Universitas Pelita Harapan, 2020)
During their teaching Field Experience Program, the researchers noticed that many students showed undisciplined attitudes during learning. The purpose this paper is to describe through a qualitative descriptive method the role of Christian teachers in building the disciplinary attitudes of grade 1 elementary school students through rewards and consequences. In Christian education, Christian teachers are called by God to help students develop character traits that are in accordance with the character of Christ, one of which is the attitude of discipline. Discipline can not grow properly without motivation. Therefore, Christian teachers need to motivate students continuously. A disciplined attitude that is instilled early on will help students have obedient personalities. The formation of students' disciplinary attitudes can be done by using rewards and consequences in the classroom. Rewards and consequences applied by Christian teachers must be guided by biblical values so that students realize that the attitude of discipline they have is not for themselves but for the glory of God. Thus Christian teachers play a very important role in shaping students' disciplinary attitudes in accordance with Christian values. Christian teachers should apply rewards and consequences to suit students' age, development, and biblical values.BAHASA INDONESIA ABSTRACT: Selama menjalani Program Pengalaman Lapangan khususnya dalam mengajar, peneliti memperhatikan banyak siswa yang menunjukan sikap yang tidak disiplin selama pembelajaran. Tujuan dari penulisan paper ini adalah untuk memaparkan peran guru Kristen di dalam membangun sikap disiplin siswa kelas 1 sekolah dasar melalui penghargaan dan konsekuensi melalui metode kualitatif deskriptif. Dalam pendidikan Kristen, guru Kristen dipanggil Tuhan untuk membantu siswa memiliki karakter yang sesuai dengan karakter Kristus, salah satunya adalah sikap disiplin. Sikap disiplin tidak dapat bertumbuh dengan baik tanpa adanya motivasi. Oleh sebab itu, guru Kristen perlu untuk memotivasi siswa secara terus menerus. Sikap disiplin yang ditanamkan sejak dini akan membuat siswa memiliki kepribadian yang taat. Pembentukan sikap disiplin siswa dapat dilakukan dengan menerapkan penghargaan dan konsekuensi di dalam kelas. Penghargaan dan konsekuensi yang diterapkan oleh guru Kristen harus berpedoman pada nilai Alkitabiah sehingga siswa menyadari bahwa sikap disiplin yang dimilikinya bukan untuk dirinya sendiri melainkan untuk kemuliaan Tuhan. Jadi guru Kristen memegang peran yang begitu penting dalam membentuk sikap disiplin siswa yang sesuai dengan nilai kristiani. Hendaknya guru Kristen dalam menerapkan penghargaan dan konsekuensi harus disesuaikan dengan usia, perkembangan, dan tentunya nilai-nilai Alkitabiah.